2011
DOI: 10.1186/1756-3305-4-175
|View full text |Cite
|
Sign up to set email alerts
|

Adult population as potential reservoir of NTD infections in rural villages of Kwale district, Coastal Kenya: implications for preventive chemotherapy interventions policy

Abstract: BackgroundNeglected tropical diseases (NTDs) are major public health problems in developing countries where they contribute to suffering of populations living in poor settings. As part of a research project started in September 2009 in Kwale district, Coast Region, Kenya, a baseline cross-sectional survey was conducted in 5 rural villages to provide information on the status of NTDs, including urinary schistosomiasis, soil-transmitted helminthiasis (STH), and lymphatic filariasis. This paper presents the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 17 publications
4
69
5
1
Order By: Relevance
“…A cross-sectional survey found the prevalence of urogenital schistosomiasis and hookworm infection among adult population in these rural villages to be 18.2% and 41.7%, respectively [10]. Kwale County is located south of Mombasa Island and borders Tanzania to the southwest and the Indian Ocean to the east.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional survey found the prevalence of urogenital schistosomiasis and hookworm infection among adult population in these rural villages to be 18.2% and 41.7%, respectively [10]. Kwale County is located south of Mombasa Island and borders Tanzania to the southwest and the Indian Ocean to the east.…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation is the lack of information on adults, preschool children, and nonenrolled school-age children. Recent reports have suggested that adults and preschool children are at risk of schistosomiasis and can contribute to transmission [30]; thus, a population based survey is required to provide an overview of schistosomiasis in the target area.…”
Section: Discussionmentioning
confidence: 99%
“…1) is situated in Kubo division. The populations of Kubo and Matuga division based on 2009 census were estimated to be 649,931 and 151,978 persons, respectively (Njenga et al, 2011). …”
Section: Study Areasmentioning
confidence: 99%
“…Subsistence farming of food crops including maize, cowpeas and cassava is done mainly for domestic consumption whereas coconuts, oranges, mangoes and cashew nuts are also grown for both domestic consumption and as cash crops. The main livestock kept include cattle, goats, ducks and chickens (Njenga et al, 2011).…”
Section: Ajavsmentioning
confidence: 99%